The Filipino family - Medina, Belen T. G. (Diliman Quezon City, Philippines : University of the Philippines Press, 2015)
This book is designed to fill the need for an introductory text on the sociology of the family as applied to the Philippine setting.
1. The study of family -- 2. Family and Kinship structure -- 3. Functions of the family and Kin group -- 4. Courtship and marriage patterns -- 5. Mate Selection -- 6. Love and Sex -- 7. Husband and wife roles -- 8. Conjugal power structure -- 9. Marital adjustment -- 10. Parenthood -- 11. The elderly -- 12. Social change and the family.
Includes index.
Keywords: FAMILY PLANNING -- PHILIPPINES